The Effect of Financial Technology and Financial Literacy on Generation Z's Financial Behavior (Case Study at SMA Sutomo 1 Medan) - Michelle; Putri Wahyuni (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine whether Financial Technology and Financial Literacy have a significant effect on the Financial Behavior of Generation Z at SMA Sutomo 1 Medan. This research uses quantitative data methods and the data source is primary data. The population in this study were 892 students of SMA XII class at Sutomo 1 Medan. The sample in this study were students who were ? 17 years old, and students who majored in social studies, totaling 134 respondents using Purposive Sampling data collection technique. Data analysis and testing consists of validity test, reliability test, descriptive statistics, classical assumption test, multiple linear regression analysis, partial hypothesis testing (T test) and simultaneously (F test), and coefficient of determination test. The results of this study indicate that Financial Technology has a significant effect on Financial Behavior with a T value of 2.195 > T table 1.978 and a significant value < 0.05, namely with a value of 0.030 < 0.05. Financial Literacy has a significant effect on Financial Behavior with a T value of 5.599 > T table 1.978 and a significant value < 0.05, namely with a value of 0.000 <0.05. Financial Technology and Financial Literacy have a significant effect on Financial Behavior with the value of F count 20.543 > F table 3.07 and a significant value < 0.05, namely with a value of 0.000 < 0.05. The regression coefficient value is 23.9%.